2020
DOI: 10.3390/su12072707
|View full text |Cite
|
Sign up to set email alerts
|

When a Girl Awakened the World: A User and Social Message Analysis of Greta Thunberg

Abstract: Young climate activist Greta Thunberg was Time magazine’s Person of the Year for 2019. In this study, the authors examine the role of social media in Thunberg’s rise to prominence by investigating Twitter communications over 14 months, analyzing tweet contents and user profiles. The changes in sentiment revealed on Twitter are examined, along with four major events from the period. The paper also compares Swedish and American user characteristics in relation to Thunberg. The findings reveal that celebrities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 20 publications
0
48
0
6
Order By: Relevance
“…Similarly, Greta Thunberg could be considered another ambivalent phenomenon in ASD that creates high expectations, but with conflicting positions. She is a young activist with Asperger’s who has been named Person of the Year by Time magazine, but who in turn has been the subject of harsh criticism from certain internet users [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Greta Thunberg could be considered another ambivalent phenomenon in ASD that creates high expectations, but with conflicting positions. She is a young activist with Asperger’s who has been named Person of the Year by Time magazine, but who in turn has been the subject of harsh criticism from certain internet users [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the content offered on the websites corresponds to myths, hoaxes, fallacies, sensationalism, creating controversy, etc., as in the following cases: false myths about vaccines [ 14 ]; misleading cures for the disorder [ 15 ]; attributing death to the diagnosis itself [ 8 ]; or the controversy and curiosity generated by the “Greta phenomenon” [ 16 , 17 , 18 ]. In other cases, the same platforms can act as standardization, awareness, and inclusion tools.…”
Section: Introductionmentioning
confidence: 99%
“…The latter option is crueler and considered cyberbullying, but the former is perhaps more disheartening, as it shows the stigma and misinformation surrounding autism. Jung et al [ 35 ] examined 1.7 million tweets related to Thunberg, and the results also showed, through sentiment analysis, that she was a controversial figure who stirred both positive and negative tweets. The authors also concluded that political polarization heavily influenced the analyzed tweets.…”
Section: Discussionmentioning
confidence: 99%
“…Even if there is a risk of misinformation on both sides of the climate change debate, a tension is embodied in the social media and media coverage of activist Greta Thunberg (Jung, Petkanic, Nan, & Hyun Kim, 2020), via whom a rising awareness of the general public has developed. The knowledge that drastic changes need to be made quickly to meet the requirements to lower CO 2 emissions globally according to the Paris Agreement can cause 'eco-anxiety,' a high level of stress in the individual (Mkono, 2019).…”
Section: Ethical Obligationsmentioning
confidence: 99%